Edukasi Dengan Metode Audiovisual Sebagai Upaya Peningkatan Pengetahuan Kader Mengenai Bahaya Tersedak Pada Bayi - Noerma Shovie Rizqiea; Ratih Dwilestari Puji Utami (Jurnal Empathy Pengabdian Kepada Masyarakat, 2020)
Background: Children are uniquely vulnerable to a variety of emergency situations. These situations are often life-threatening if not treated quickly and effectively. Infants and young children are at higher risk for respiratory emergencies than adolescents or adults. Young children often lack coordination, which makes them prone to choking on food and small objects, which can also lead to cardiac arrest. The aim of this community service is that after receiving health education and demonstrations about the dangers of choking, it hopes that an increase in cadres' knowledge of the dangers of choking at the Posyandu for toddlers, Sadar Ibu I, Dusun Jetak. Methods: Respondents involved were 14 cadres of Posyandu Toddler Sadar Ibu I Dusun Jetak. Activities carried out online. The activity began with a pre-test, then continued with provisions health education using audio-visual video media, and ended with a post-test measurement. Results: The percentage of knowledge of cadres during the pre-test showed that 3 cadres (21%) had good knowledge, and the remaining 11 cadres (79%) had less knowledge. The post-test results showed that 10 cadres (71%) had good knowledge, and the remaining 4 cadres (29%) still had a bad knowledge. Conclusion: Increase Cadre's knowledge of the dangers of choking on babies.